Free radial forearm flap after partial glossectomy for squamous cell carcinoma of the tongue - Chuah, U.C.; Kamarul, Tunku; Ahmad, T.S. (Faculty of Medicine, University of Malaya, 2006)
Squamous cell carcinoma of the tongue is a highly malignant condition and results in high mortality and morbidity in patients despite its early detection (1). Early surgical interventions have been found to reduce mortality but in many reports, tongue reconstructions using live grafts have been found to reduce normal tongue function of speech, swallow and taste. In contrast, our report using free radial forearm flap (FRFF) to reconstruct the defect left over after a radical tongue resection in a 38-year-old gentleman with oral cancer has shown promising results. This type of reconstruction has left the patient with a functional and cosmetically acceptable tongue with minimal alteration in recognizable speech.